2021
DOI: 10.3390/jintelligence9020032
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Brain and Cognition: A Multilayer Network Analysis of Brain Structural Covariance and General Intelligence in a Developmental Sample of Struggling Learners

Abstract: Network analytic methods that are ubiquitous in other areas, such as systems neuroscience, have recently been used to test network theories in psychology, including intelligence research. The network or mutualism theory of intelligence proposes that the statistical associations among cognitive abilities (e.g., specific abilities such as vocabulary or memory) stem from causal relations among them throughout development. In this study, we used network models (specifically LASSO) of cognitive abilities and brain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 90 publications
1
8
0
Order By: Relevance
“…Without directly studying this link, it remains speculative how the cognitive networks in our study relate to the alterations in brain connectivity in VP born children. Based on a behaviour-brain combined multilayer network, Simpson-Kent et al (2021) concluded that such relations are complex and not necessarily straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…Without directly studying this link, it remains speculative how the cognitive networks in our study relate to the alterations in brain connectivity in VP born children. Based on a behaviour-brain combined multilayer network, Simpson-Kent et al (2021) concluded that such relations are complex and not necessarily straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…They enable the simultaneous modelling of multiple routes to a specific outcome and can incorporate multidirectional interactions across levels of description. They can therefore be used to test competing theories about how abilities are related across groups and/or time points, and to characterise how genetic, neural, and environmental factors influence these relationships (e.g., Isvoranu et al, 2020; Simpson-Kent et al, 2021). Such applications will be crucial for building an understanding of not only how abilities are related but also which mechanisms enable their wiring.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the need for more studies with multilayer networks (network of networks) is highlighted since they allow better statistical accuracy of the joint use of neurophysiological and psychological data [81,82]. This may be important in the current pandemic context, as COVID-19 can affect the central nervous system and cause neuropsychiatric disorders [83].…”
Section: The Use Of Psychological Network Models In the Context Of Ne...mentioning
confidence: 99%